Living with COVID-19 pandemic – Emerging challenges for ultrasound physicians and their suggested solution - Shagufta Malik ,Musab Riaz (Journal of Rawalpindi Medical College, 2020)
Background: The recent coronavirus disease (COVID-19) pandemic is a serious health concern with far-reaching implications in every facet of human life. New challenges have emerged for ultrasound physicians engaged in diagnostic ultrasound examinations. Methods: Based on a comprehensive literature review the author has suggested a few precautionary measures that should be incorporated by the ultrasound physicians in their practice against the spread of coronavirus disease. Suggestions: Multi-level safeguard checks before, during, and after the ultrasound examination are suggested to protect ultrasound physicians, staff, and patients from COVID-19. The importance of triage for patient screening is stressed. Also, limiting patients by deferring non-urgent cases and cancelling aerosol-generating procedures is recommended. The need of counselling of patients and staff is stressed regarding the importance of facemasks, hand hygiene, and safe distancing. Incorporating different types of barriers against the virus such as facemasks, face-shields, personnel protective suits for ultrasound physicians and staff, and shielding the equipment and transducer with disposable or wipeable plastic sheets is suggested. Besides, the significance of cleaning and disinfection of the examination room and equipment by suitable disinfectants after each patient and at the end of the day is highlighted. Conclusion: Learning to live with the COVID-19 pandemic is the need of the day both for the general public and medical community. Being members of the medical community ultrasound physicians should gear up to the emerging challenges of COVID-19 to protect themselves, their patients, and allied healthcare staff from coronavirus infection.